Visual‐search observers for assessing tomographic x‐ray image quality. Issue 3 (1st March 2016) - Gifford, Howard C.; Liang, Zhihua; Das, Mini
Abstract : Purpose: Mathematical model observers commonly used for diagnostic image‐quality assessments in x‐ray imaging research are generally constrained to relatively simple detection tasks due to their need for statistical prior information. Visual‐search (VS) model observers that employ morphological features in sequential search and analysis stages have less need for such information and fewer task constraints. The authors compared four VS observers against human observers and an existing scanning model observer in a pilot study that quantified how mass detection and localization in simulated digital breast tomosynthesis (DBT) can be affected by the number P of acquired projections. Methods: Digital breast phantoms with embedded spherical masses provided single‐target cases for a localization receiver operating characteristic (LROC) study. DBT projection sets based on an acquisition arc of 60° were generated for values of P between 3 and 51. DBT volumes were reconstructed using filtered backprojection with a constant 3D Butterworth postfilter; extracted 2D slices were used as test images. Three imaging physicists participated as observers. A scanning channelized nonprewhitening (CNPW) observer had knowledge of the mean lesion‐absent images. The VS observers computed an initial single‐feature search statistic that identified candidate locations as local maxima of either a template matched‐filter (MF) image or a gradient‐template MF (GMF) image. Search inefficiencies that modified the statistic were also considered. Subsequent VS candidate analyses were carried out with (i) the CNPW statistical discriminant and (ii) the discriminant computed from GMF training images. These location‐invariant discriminants did not utilize covariance information. All observers read 36 training images and 108 study images per P value. Performance was scored in terms of area under the LROC curve. Results: Average human‐observer performance was stable for P between 7 and 35. In the absence of search inefficiencies, the VS models based on the GMF analysis provided the best correlation (Pearson ρ ≥ 0.62) with the human results. The CNPW‐based VS observers deviated from the humans primarily at lower values of P . In this limited study, search inefficiencies allowed for good quantitative agreement with the humans for most of the VS observers. Conclusions: The computationally efficient training requirements for the VS observer are suitable for high‐resolution imaging, indicating that the observer framework has the potential to overcome important task limitations of current model observers for x‐ray applications.